1994
DOI: 10.1088/0960-1317/4/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Electrically activated normally closed diaphragm valves

Abstract: Thermal actuation of integrated valve structures is attractive due to the relative simplicity of the actuator design, the moderate activation time possible, the relatively low total power required, and the ability to fully integrate the actuator with the flow control component. Of the many thermal actuation schemes, the use of bimetallic elements is preferred, particularly when a low cost, fully integrated structure is desired. Bimetallic structures allow both normally-open and normally-closed valves by varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…The schematic of the thermally actuated microvalve developed by Jerman [58,59] is shown in Figure 2 A micromachined bimorph pressure-driven actuated valve developed by Trah et al [60] is shown in Figure 2 Lisec et al [61] developed a normally closed design based on buckling of the support beams attached to a mesa. A schematic diagram of the valve is given in Figure 2.4.24.…”
Section: Thermal Actuationmentioning
confidence: 99%
“…The schematic of the thermally actuated microvalve developed by Jerman [58,59] is shown in Figure 2 A micromachined bimorph pressure-driven actuated valve developed by Trah et al [60] is shown in Figure 2 Lisec et al [61] developed a normally closed design based on buckling of the support beams attached to a mesa. A schematic diagram of the valve is given in Figure 2.4.24.…”
Section: Thermal Actuationmentioning
confidence: 99%
“…Many efforts have been made to develop various microvalves to meet different requirements for specific applications [2][3][4][5][6][7][8][9]. Though the configurations of these valves could be different (open or closed valve), the structures are very similar.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the actuator's stroke and the forces delivered are limited. Table 1 gives an overview of earlier demonstrated microvalve [3][4][5][6][7][8][9]. Some of these valves meet most of the requirements, such as high inlet pressure, low leakage and process gas isolation but have relatively low flow rates [2,3,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Moving parts, in most cases membranes fabricated of silicon or additionally required active or passive valves, may result in short lifetime and low reliability. Displacement pumps with bimetallic [2], electrostatic [3,4], thermo-pneumatic [5,6], piezoelectric [7,8] and other drivers [9] have been reported. The properties of those systems regarding long term stability are still not known.…”
Section: Introductionmentioning
confidence: 99%